(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Tourism has emerged as a significant global industry, and is considered the industry of the future due to its impact on the economy and its potential for sustainability in terms of environmental, economic, and social dimensions. This industry is recognized as the most civilized and least environmentally polluting. In terms of sustainable development, tourism plays a crucial role in preserving cultural balance at tourist sites and maintaining attractive elements In our research, we try to show the importance of religious tourism sites in achieving sustainability, and the most important conclusions were, sustainability translates into options, and each option has a "real cost", which is the sum of the environmental, social and economic costs in exchange for the benefits accruing from each option. On the practical side, the research dealt with three paragraphs It was represented by the main dimensions of sustainability, which are the economic dimension, the social dimension and the environmental dimension, where the first paragraph (economic sustainability) achieved the highest percentage in terms of the arithmetic mean, followed by the second paragraph (social sustainability) in terms of arrangement Among the recommendations is coordination between local governments, religious shrines, Shiite shrines and the central government in order to activate the mechanisms of sustainability in the province of Najaf